A Study of Airlines Customer Satisfaction in the Kingdom of Saudi Arabia - Althaqafi, Sultan; Bashammakh, Hani Ali; Albarmawi, Youssif; khan, Khalid; Qazi, Sayeeduzzafar (European Scientific Journal, ESJ, 2019)
The quality of service plays a major role in service industry especially when it comes to customer satisfaction level. This paper focuses on investigating the customer’s satisfaction levels towards services provided by Saudi Airlines. For this purpose, a questionnaire was developed and distributed among 165 domestic as well as international passengers at the airport. After scrutiny, it was found that only 159 questionnaires were completed in all respects and were included in the study. The data collected afterwards were analysed in order to measure the actual satisfaction level of customers. It was found that the domestic as well as the international passengers of Saudi Arabia airlines were not happy and satisfied with the services provided by the airlines. Thus, the major problem area includes baggage handling, treatment of passengers at airport in case of any grievances, food quality, and entertainment on board. Based on the outcome of the research, certain strategies to overcome such issues were recommended by the authors.